(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The study was conducted to evaluate the present status of the production of traditional fermented fish product - shidal (Chapa shutki or shidol) in Lalpur, Ashuganj Union, Brahmanbaria district and its ecological implication and value chain during June to November, 2016. Shidal is produced by natural fermentation process of fresh water punti and marine phaisha and poa fish during winter (October to January). It was found that the Shidal production from freshwater fish in Lalpur has been shrinking gradually due to a decline in fish production from the Meghna River Basin and low supply of raw fishes from others areas. The fishers noted the local extinction of large numbers of once common fish with a gradually low supply of punti and a declining average size among the fishes that are still captured. It was found that not only the total volume of catch decreased but there have been a marked decline in catch per unit effort (CPUF) over the last ten years. During the fermentation season, every day 2-4 ton of raw punti are sold in Lalpur Fish Landing Center and the price of punti varies with grade, season and quality. On an average 4 kg of fresh punti produces 1.2 kg of dry punti and 1.2 kg of dry punti produces 1.44 kg of shidal. It was observed that there were two types of punti used for making shidal in Lalpur - with scales and without scales. The prices of shidal were Tk 800/kg, Tk 500/kg, and Tk 500/kg produced from punti, poa and phaisha, respectively. There are nearly 250 dangaries (fish processing place) for Shidal production and each of the danagaries produce 100-150 motkas (each motka contains 36-40 kg of shidal) of shidal in a season. One motka is sold in Tk. 20,000-24,000 when there is no salt used but Tk. 16,000 per motka when salt is used. It was found that around 2000 people were employed in Shidal production and another 200 people worked in filling in the motka in Lalpur. No chemical are used to make Shidal but some salt is applied during Shidal processing. It was observed that there was no fixed marketing channel for Shidalshutki. Seventy percent (70%) of the Shidal are produced for the domestic market. Shidal produced from small sized punti are exported to India but Shidal produced from marine fishes has never been exported. Although people prefer Shidal made from punti, but due to its gradual disappearance from the natural water bodies, they are forced to consume Shidal prepared from marine poa or phaisa. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (2), 159-172